Aligning the people in nation building - Thareja, Mannu; Thareja, Priyavrat (Gyan Management Journal, 2012)
People resurrected Japan once again. These involved people were special people who supported the masses and rejuvenation processes. It was a repeat of Japanese mapping a/The Total Quality Control paradigm, which marked that there should be a continual comfort for the people, even when the large environment went bad. Such people build even nations as derived from the Congruence Model of O’Reilly and Tushman1 Right from how various people react to the exigencies, the people make or mar the organizations. However Japan demonstrated that there were good people who up from supporting the authorities, graduated to provide voluntary support and even augment resources by spearheading® risking one’s own life.In the present work, an attempt is made to review the learning from recent Japan’s calamity, and thereafter make an analytical reprise of the role people performed. Since the contribution is exemplary, a new kind of people competency - say detourers has been proposed augmenting the initial four proposed by Philips viz., Optimizers, Firefighters, Forecasters, Creators. These make the people competencies fine five.